Vietnamese Attitudes and Behavioural Patterns towards Counterfeit Brands - Huynh, Giang; Wilson, Jonathan A.J. (ASEAN Marketing Journal, 2021)
This study examines Vietnamese female consumers’ attitudes towards counterfeit branded products; by investigating the influence of brand image, product involvement and price advantage towards decision-making processes associated with purchasing and ownership. An inductive anti-positivist approach was adopted, employing qualitative methods; drawing from in-depth interviews distilled and synthesized using Word Cloud software, as Geographic Information System (GIS) based Spatial Analyses. Findings suggest that Price Advantage plays a determining and predominant role in encouraging consumers’ purchase intention of a counterfeit product. In addition, Brand Image has positive effect on the purchase intention as well; while product involvement plays no significant role in the process. Further observations point to there being paucity of literature that focuses on Vietnamese and ASEAN markets. With this is mind, a new conceptual framework was developed to reflect the nuances of the Vietnamese consumer experience; which it is suggested will be of value to scholars, practitioners and further studies.